The treatment ideal and detention reality: Demographic, professional/ occupational and organizational influences on detention worker punitiveness - Bazemore, Gordon (American journal of criminal justice, 1994)
For some time, corrections researchers have focused on the punitive and rehabilitative orientations of correctional officers. Relatively little research attention, however, has been devoted to understanding the support for these orientations among correctional workers responsible for the care and custody of juvenile delinquents. Based on survey data drawn from a sample of detention care workers (DCWs) in two facilities in a Southeastern state (N=109), this paper examines the extent to which, and why, DCWs adopt a punitive orientation to youth in detention despite policies and training that discourage this view. Findings, that contrast the relative impact of demographic, occupational/professional and organizational environment variables in accounting for variation in punishment/control orientation among DCWs, suggest that demographic indicators (i.e., age, gender) and organizational environment contribute disproportionately to explained variance in punitive orientation once other variables are controlled. Implications for detention policy, staff recruitment and training are discussed.